The signalling value of public issue and offer for sale ratios on the performance of initial public offers / Lin Yong Tong and Rubi Ahmad - Lin, Yong Tong; Ahmad, Rubi (Penerbit UiTM (UiTM Press), 2018)
Investors of initial public offers (IPOs) rely on the prospectus for important information about the company. But the motivation of the issuers (original shareholders) for going public is unknown and hidden from the investing public, making the IPO investment a risky venture. Based on the Signalling Theory, we postulate that the public issues (PI) and offer for sale (OFS) ratios to contain properties to signal the intention of the issuers at time of listing. Our samples are collected from the Bursa Malaysia from 2002 to 2008 and the performances are tracked till 2011. The regression results are consistent with the Signalling Theory which stipulates that when issuers sell down their stakes, it sends a gloomy signal, even though the offer of OFS does not cause any dilution to company’s value. In addition, small companies with high OFS ratio record weaker long-run performance than large companies.